(3HgLI GdegL aj HYV aVGFd GdWGFa hhLs - (3CMeO Hf Ydj Hf CHj HcQ GdYHOQj GdCfOdSj GdejhQbj, CHh GdYHGSs ((3ecI GdecQeI s)
(3ChdgG (B:s
(3bGd GdQGLi dehdGgCMeO GHf Ydi GdYHOQi CeG HYO aEf PcQ eKhi GdCeg YHO Gddg Hf YHGS s
(3BNQgG (B:s
(3hjGQH NQdi ai GdCehQ hYGafi hWjH di GdOGQjf jGNjQ hGgH hGdMeO ddg QH GdYGdejf s
(3fbdJ Yf fSNI SbjeI GdNW cJHJ (B1093s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B635 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B52 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs